2020
DOI: 10.1002/aenm.202001788
|View full text |Cite
|
Sign up to set email alerts
|

Nonfullerene Acceptors: A Renaissance in Organic Photovoltaics?

Abstract: Efficient, low‐cost, and low‐embodied energy photovoltaics are key enablers of the global decarbonization agenda. In addition to the market‐leading crystalline silicon technology, several other promising candidates are under active investigation with the perovskites leading the way with single‐junction efficiencies exceeding 25% at the lab‐scale. So‐called organic photovoltaics (solar cells based upon organic semiconductors), particularly those that can be solution processed, have long promised the Nirvana of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 47 publications
0
87
0
Order By: Relevance
“…[ 43–45 ] In 2017, NIR‐absorbing non‐fullerene or fused ring electron acceptors (NFAs or FREAs) created a new wave in OSCs. [ 46 ] Since then, significant efforts have been made to enhance the performance of ST‐OSCs by incorporating both LBG PDs and NFAs or FREAs as the photoabsorbent layer, leading to remarkable PCEs of up to 14.1% in only 3 years via efficient extraction of photons in the NIR region. [ 31,47–50 ] Subsequently, it has become vital to gain insight into the role of these newly designed photoabsorbent materials in boosting the PCEs of ST‐OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 43–45 ] In 2017, NIR‐absorbing non‐fullerene or fused ring electron acceptors (NFAs or FREAs) created a new wave in OSCs. [ 46 ] Since then, significant efforts have been made to enhance the performance of ST‐OSCs by incorporating both LBG PDs and NFAs or FREAs as the photoabsorbent layer, leading to remarkable PCEs of up to 14.1% in only 3 years via efficient extraction of photons in the NIR region. [ 31,47–50 ] Subsequently, it has become vital to gain insight into the role of these newly designed photoabsorbent materials in boosting the PCEs of ST‐OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, we developed an intuitive experiment‐oriented data‐driven ML model for polymer:non‐fullerene small molecule acceptor (NFA) OPVs (the ML dataset and screened polymers are extracted from experimental data). Polymer:NFA OPVs have evolved rapidly over the past few years, [ 42–45 ] with the maximum PCE of a single‐junction solar cell increasing from 12% in 2016 [ 46 ] to 14% in 2018 [ 47 ] and 18% in 2020; [ 48–51 ] in contrast, the PCE of polymer:FA OPVs has remained stable at ≈11%. Although some studies reported the ML‐driven development of polymer:NFA OPVs, [ 28–33 ] there still remain possibilities for efficient conjunction between ML and experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Rapid progress over the past 3 years have seen efficiencies exceed 18% with the so‐called D18:Y6 system, [ 7 ] with predictions of breaking the 20% barrier in the next 12 months or so. [ 8 ] Historically, detailed mechanistic understanding lags advances in new materials design and development in the field of OPV. This is also the case for the NFAs which seem to present quite different structure‐property relationships to the fullerenes–particularly in relation to the electro‐optical and thermodynamic rule books.…”
Section: Introductionmentioning
confidence: 99%